Analisis Nilai-nilai Moral dalam Cerita Rakyat Bengkulu Burung Berak Emas - Irfan Achmad Fauzi; Abdul Muktadir (Universitas Bengkulu, 2023)
This study aims to determine the moral values ​​contained in the Bengkulu folklore about the legend of the golden bird. This moral value is reflected in the behavior and actions of the characters in each character in the story. The method used in this research is qualitative descriptive analysis. The type of source data is a document or archive in the form of Bengkulu folk tales taken from the Rejang folklore book. The data analysis technique uses the Conten Analysis technique (content analysis). The results showed that in Bengkulu folklore, the Legend of the Golden Bird, there is a value of human relations with oneself, (b) the value of human relationships with other humans in the social sphere including relationships with the environment, and (c) the value of human relations with God. The value of human moral relationship with oneself is in the form of hard work, determination, intelligence, realistic life, honesty, generosity, courage, humility, patience, courtesy, toughness, right promises, and diligence. The value of human moral relations with other humans in the social sphere includes relationships with the natural environment in the form of good attention to others, living in harmony, cooperation, apologizing, seizing, appreciating, respecting parents, advising, helping, feeling openness, envy, and feeling affection. The value of the moral relationship between humans and God is in the form of gratitude, God is the recipient of the reward.